2018
DOI: 10.1021/acsami.8b14677
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastable Luminescent Organic–Inorganic Perovskite Quantum Dots via Surface Engineering: Coordination of Methylammonium Bromide and Covalent Silica Encapsulation

Abstract: Encapsulation of luminescent perovskite quantum dots (QDs) into a solid matrix has been approved to be an efficient way to improve their stability. In this work, we reported a green encapsulation method to produce ultrastable CH 3 NH 3 PbBr 3 QDs incorporated into the SiO 2 matrix. Specifically, fresh-prepared CH 3 NH 3 PbBr 3 QDs were covalently embedded into silica by an aqueous sol−gel method assisted with CH 3 NH 3 Br, which not only effectively inhibited the water-driven degradation of QDs through surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…In 1845, the French chemist J. J. Ebelmen mixed SiCl 4 with ethanol to form tetraethoxysilane (TEOS) and a gel was formed during hydrolyzing in wet air. [73] Currently, this method is mostly used to fabricate the shell coating with SiO 2 , [74][75][76][77][78][79][80][81][82][83][84][85][86] TiO 2 , [84,87,88] ZrO 2 , [70] Al 2 O 3 /SiO 2 , [69] SiO 2 /ZrO 2 [89] around the surface of the MHPs core.…”
Section: Sol-gel Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In 1845, the French chemist J. J. Ebelmen mixed SiCl 4 with ethanol to form tetraethoxysilane (TEOS) and a gel was formed during hydrolyzing in wet air. [73] Currently, this method is mostly used to fabricate the shell coating with SiO 2 , [74][75][76][77][78][79][80][81][82][83][84][85][86] TiO 2 , [84,87,88] ZrO 2 , [70] Al 2 O 3 /SiO 2 , [69] SiO 2 /ZrO 2 [89] around the surface of the MHPs core.…”
Section: Sol-gel Methodsmentioning
confidence: 99%
“…Further works have also confirmed that MHPs@MO x feature enhanced photostabilities than the pristine MHP counterparts. [37,75,77,125,140] For instance, the CsPbBr 3 NC and CsPbBr 3 NC/MO 2 (M = Si, Ti, Sn) films were fabricated on the fluorine doped tin oxide substrates through a centrifugally cast process. [84] These films were exposed to the 365 nm UV light to test the photostability.…”
Section: Photostabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Hu et al, reported the silica-coated process to encapsulate CdSe/ZnS QDs in 2009 [ 31 ], but silica-coated CsPbX 3 (X = Cl, Br and I) PNPs compounds were fabricated until 2016 [ 32 , 33 ]. Subsequently, APTES [ 34 , 35 , 36 ], tetraethylorthosilicate (TEOS), and Tetramethoxysilane (TMOS) were utilized to form silica-coated CsPbX 3 (X = Cl, Br and I) PNPs.…”
Section: Introductionmentioning
confidence: 99%